Identifikasi Ruang Terbuka Hijau (RTH) Di Kota Ambon - Risqi Mumpuni Dyastuti (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: Greenery open space proportion in the city is, at least, 30 (thirty) percent of the city area. The proportion for public greenery open space (GOS) in the city is, at least, 20 (twenty) percent of the city area. Meanwhile, the proportion for private greenery open space (GOS) in the city is 10 (ten) percent. Hence, the proportion identification is needed, and availability of greenery open space (GOS) in Ambon City is adjusted with the provision of Act Number 26 of 2007 concerning Spatial Planning.Purposes of the Research: This research aims to identify the proportion and availability of greenery open space in Ambon.Methods of the Research: This research is doctrinal research using secondary data. The secondary data used is primary legal material, secondary legal material, and tertiary legal material. Library research is used as technique of data collection. Furthermore, technique of analysis data used in this research is qualitative data analysis with historical approach.Results of the Research: The Significance of total population also affects the decrease of air quality in the environment. The decrease of environmental quality can be returned by preserve the amount of greenery open space as stated in the applicable statutory provisions. The availability of greenery open space is also affected by the remaining amount of carbon dioxide emissions produced both from motorized vehicles and humans, because the carbon dioxide produced is directly proportional to the population. Total carbon dioxide emissions produced is 393,295.56 ton/year. Thus, the need of Greenery Open Space in Ambon is 10,783.39 ha, with details; greenery open space for public is 7,188.92 ha and for private is 3,594.46 ha from total population of 371,650 people with area of 35,944.62 ha. The need for ideal greenery open space in Ambon is still sufficient to absorb the remaining carbon dioxide emissions.